Using blockchain in the follow‐up of emergency situations related to events. (18th December 2019) - Rivero‐García, Alexandra; Santos‐González, Iván; Hernández‐Goya, Candelaria; Caballero‐Gil, Pino
Summary: This paper describes a decentralized low‐cost system designed to reinforce personal security in big events in case of emergency. The proposal consists of using smart contracts supported by blockchain in the management of events. An alternative communication channel that does not require any cloud service is also provided with the aim of improving the coordination of emergency services. Peers may use this emergency support tool to interact with each other through a chat when additional support is required. Since information security is mandatory in this scenario, identity‐based signcryption schemes are here used to guarantee communication confidentiality, authenticity, and integrity. Depending on the communication mode (peer‐to‐peer or broadcast), different signcryption methods are used. A first implementation of the proposal has produced promising results.